Effects of grain size and temperature on mechanical properties of Fe–20Mn–0.7C TWIP steel. Issue 1 (2nd January 2020) - Li, Guoyang; Wang, Yuhui; Chen, Xiaoman; Xiong, Jianchao; Tian, Yanzhong; Cao, Wenquan; Wang, Tiansheng
ABSTRACT: Fe–20Mn–0.7C twinning-induced plasticity (TWIP) steel with the grain sizes in the range 1.7–10.2 μm was produced by cold rolling and annealing. The effects of grain sizes on the mechanical properties of the TWIP steel were studied by tensile test at room temperature (RT) and –180°C. The yield strength increased with decreasing grain size at RT and –180°C, and the corresponding Hall–Petch relationships were established at both temperatures and are as follows (i) σ 0.2  = 205 + 453 d –1/2 (at RT) and (ii) σ 0.2  = 317 + 755 d –1/2 (at –180°C). When the temperature decreased from RT to –180°C, the stacking fault energy decreased from 24to 17.9 mJ/m 2, approximately 25%, and the deformation mode is transformed from deformation twins to martensite transformation.